Efecto de la orciprenalina sobre la función pulmonar en pacientes con procesos obstructivos y restrictivos - Cruz, Julio C. (2024)
The effect of orciprenaline on pulmonary function has been studied in 21 patients, 10 with bronchial obstruction (group I) and 11 with restrictive diseases (group II), of both sexes. The drug was used in oral form (40 and 80 mgr/day) during 10 days. Lung volumes, airway resistance, alveolar-arterial O2 and CO2 tension differences, venous admixture, CO diffusing capacity and acid-base status was determined before and after treatment.  The changes observed depended on individual way of response. The bronchodilating effect of orciprenaline produced, in some cases, normalization of lung volumes in patients with hyperinflation, or making the restrictive pattern more evident in patients of this kind. In others, there was an improvement of alveolar ventilation, reduction of VD/VT ratio or decreasing the CO2 gradient, suggesting less uneveness of ventilation-perfusion ratios. Six patients from group 1 and 3 from group II showed significant increase in arterial oxygen tension. Three patients of each group showed significant changes in plasma bicarbonate regulating the acid-base balance. Modifications of CO. diffusing capacity were due to alveolar ventilation or/and functional residual capacity changes. It is important to emphasize that some patients decreased their arterial oxygen tension and/or increased CO2 ´producing respiratory acidosis. Due to these opposing responses between patients, statistical analysis of differences were not significant.  In conclusion, treatment with oral bronchodilating drugs does not always imply a reduction of airway resistance. Independent of this change, it is posible to observe modifications in alveolar ventilation, oxygenation and acid-base balance. Therefore, ventilatory and volume measurements that are used yo evaluate bronchodilating drugs, do notallow to predict the ventilatory efficiency of the patients studied. It is necessary to know arterial O2 and CO2 tensions. To understand the mechanisms involved, additional test as those performed in the present study, are required.